How Relevant Is Targeting to the Success of an Antipoverty Program? - Ravallion, Martin (World Bank, 2012)
Policy-oriented discussions often assume that "better targeting" implies larger impacts on poverty or more cost-effective interventions for fighting poverty. The literature on the economics of targeting warns against that assumption, but evidence has been scarce and the lessons from the literature have often been ignored by practitioners. This paper shows that standard measures of targeting performance are uninformative or even deceptive about the impacts on poverty, and cost-effectiveness in reducing poverty, of a large cash transfer program in China. The results suggest that in program design and evaluation, it would be better to focus directly on the program's outcomes for poor people than to rely on prevailing measures of targeting.